Role of Work Satisfaction as Mediating Variable in Relationship Between Organizational Commitment, Compensation and Employee Performance in Porcelain Industry - Najihatul Faridy; Endang Fatmawati; Uli Wildan Nuryanto; Joko Ariawan; Deddy Novie Citra Arta (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objectives to be achieved in this study are to identify and analyze the effect of organizational commitment, job satisfaction and compensation on employee performance and to analyze the effect of compensation and organizational commitment on employee performance in the porcelain industry. Total population of 120 employees. Time of research conducted by researchers for 3 months. The research was conducted from March to May 2022. The data obtained from the results of the questionnaires will then be processed and analyzed with the aim of turning the data into information. Data processing and analysis was carried out using the SPSS version 23 program. The data analysis method used was multiple linear regression method. The result of the study is that organizational commitment has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Organizational commitment and compensation simultaneously have a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Compensation has a positive and significant effect on job satisfaction. Organizational commitment has a positive and significant effect on job satisfaction. Organizational commitment and compensation simultaneously have a positive and significant effect on employee performance through job satisfaction.